081 Impact of co-morbid PCOS on IIH outcomes. Issue 9 (12th August 2022) - Thaller, Mark; Homer, Victoria; Wakerley, Benjamin; Mollan, Susan; Sinclair, Alexandra
Abstract : Introduction: Idiopathic intracranial hypertension (IIH) and Polycystic ovary syndrome (PCOS) affect women of reproductive age with obesity but have different hyperandrogenic profiles. The prevalence of comorbid PCOS in IIH patients is highly variable in the literature; and the longitudinal impact on visual and headache outcomes are unknown. Aims and Methods: Assess the prevalence in a prospective IIH cohort (IIH Life database (2013-2021)) based on Rotterdam criteria from questionnaire and routine clinical practice data. Secondary aim to evaluate the impact of PCOS on IIH outcomes (visual and headache). Results: 382 females with IIH were followed up for a median 10 (0-87) months and had presence or absence of PCOS documented. Prevalence of PCOS in IIH was 20.4% (78/382) by the Rotterdam criteria, with additional 15.2% (58) describing hyperandrogenism alone. Females with IIH and comorbid PCOS did not have significantly different visual or headache outcomes (including mean deviation and optical coherence tomography papilloedema measures). Conclusions: Symptomatic hyperandrogenism is common in IIH patients who have previously been noted to have elevated levels of testosterone. Diagnosing co-morbid PCOS is important as it can impact fertility and long-term cardiovascular risk. From an IIH management aspect, comorbid PCOS does not confer worse visual or headache outcomes.